A fast and remote screening method for sub-micro-structuration in pressurized mixtures containing water and carbon dioxide - Stehle, Simon; Lay, Ebrahim Nemati; Triolo, Alessandro; Ventosa, Nora; Braeuer, Andreas Siegfried (Journal of Supercritical Fluids, 2019)
We present a fast optical screening method for the detection of sub-micro-structures nanostructuration in water-containing fluids. The optical method is based on Raman spectroscopy of the water stretching vibration. The shape of this Raman band reveals information about the development of hydrogen bonds, from which it can be extracted whether the water molecules are homogeneously distributed in the mixture, or they are heterogeneously distributed (sub-micro-structuration). The fast screening is enabled by analyzing the potentially structured ternary system CO2/acetonitrile/water between 10 and 22 MPa and at 308 K, 318 K and 328 K in continuously spilled microcapillary system (MCS). Compared to batch systems we specify the advantages of the MCS in which the operational conditions with respect to pressure, temperature and composition can be changed fast, reproducibly and across a wide range.
CRIS-Team Scopus Importer:2019-06-28
Keywords: High pressure microfluidics; Hydrogen bond; In situ Raman spectroscopy; Nanostructuration; Supercritical carbon dioxide

Determination of Vapor Liquid Equilibrium Data in Microfluidic Segmented Flows at Elevated Pressures Using Raman Spectroscopy - Luther, Sebastian; Bräuer, Andreas; Weihs, Kristian; Will, Stefan; Stehle, Simon (Analytical Chemistry, 2015)
A fast, noninvasive, and efficient analytical measurement strategy for the characterization of vapor liquid equilibria (VLE) is presented, which is based on phase (state of matter) selective Raman spectroscopy in multiphase flows inside microcapillay systems (MCS). Isothermal VLE data were measured in binary and ternary mixtures composed of acetone, water, carbon dioxide or nitrogen at elevated pressures up to 10 MPa and temperatures up to 333 K. For validation, the obtained data were compared with literature data and reference measurements in a high-pressure variable volume cell. Additionally, the mixtures were investigated at temperatures and pressures where no data is available in literature to extend the high-pressure VLE database.

Hydrogen Bond Networks in Binary Mixtures of Water and Organic Solvents - Stehle, Simon; Braeuer, Andreas Siegfried (Journal of Physical Chemistry B, 2019)
We here present an approach for the optical in situ characterization of hydrogen bond networks (HBNs) in binary mixtures of water and organic solvents (OSs), such as methanol, ethanol, and acetonitrile. HBNs are characterized based on (i) the analysis of experimental molar Raman spectra of the mixture, (ii) partial molar Raman spectra of the mixture constituents, and (iii) computed ideal molar Raman spectra of the mixture. Especially, the consideration of the partial molar Raman spectra provides insights into the development of hydrogen bonds of molecules of one species with their neighbors. The obtained Raman spectra are evaluated with respect to the centroid of the symmetric stretching vibration Raman signal of water and to the hydroxyl stretching vibration of alcohols. We show the influence of composition and temperature on the development of the HBN of the mixtures, the HBN of water, and the HBN of the OS molecules.
CRIS-Team Scopus Importer:2019-06-04